Association of Neighborhood Socioeconomic Status With Outcomes in Patients Surviving Stroke. (25th May 2021) - Stulberg, Eric L.; Twardzik, Erica; Kim, Sehee; Hsu, Chia-Wei; Xu, Yuliang; Clarke, Philippa; Morgenstern, Lewis B.; Lisabeth, Lynda D.
Abstract : Objective: To examine associations between neighborhood socioeconomic status (nSES) and 90-day poststroke outcomes. Methods: The Brain Attack Surveillance in Corpus Christi Project is a population-based surveillance study in Nueces County, Texas. Patients with strokes were identified between 2010 and 2016 via active and passive surveillance and enrolled in the study. nSES index is a standardized composite of 2010 Census tract–level income, wealth, education, and employment (median −4.56, interquartile range −7.48 to −0.46). The 90-day outcomes were ascertained via interview: functional status measured by the average of 22 activities of daily living/instrumental activities of daily living (range 1–4), biopsychosocial health by the Stroke-Specific Quality of Life scale (range 0–5), and depressive symptoms by the 8-item Patient Health Questionnaire (range 0–24). Associations between nSES and outcomes were estimated using confounder-adjusted generalized estimating equations with an nSES × NIH Stroke Scale score interaction term. Results: Seven hundred seventy-six survivors made up the analytical sample (52.96% male, 62.24% Mexican American, 52.96% ≥64 years old). Higher compared to lower nSES (mean difference comparing 75th to 25th percentile of nSES) was associated with better function (−0.27, 95% confidence interval [CI] −0.49 to −0.05), better biopsychosocial health (0.26, 95% CI 0.06–0.47), and fewer depressive symptoms (−1.77, 95% CI −3.306 to −0.48) among those with moderate to severe strokes. Among those with minor strokes, higher nSES was associated with better function (−0.13, 95% CI −0.24 to −0.02). Conclusions: nSES may influence poststroke recovery. Studies should identify neighborhood characteristics that contribute to poststroke outcomes, particularly in moderate to severe stroke survivors.